A Preliminary Exploratory Study of Autologous Fat Transplantation in Breast Augmentation With Different Fat Transplantation Planes - Li, Bin; Quan, Yuping; He, Yufei; He, Yunfan; Lu, Feng; Liao, Yunjun; Cai, Junrong (Frontiers in Surgery, 2022)
Background Autologous fat transfer is common in breast augmentationor reconstruction. However, AFG recipient site in the breast for fat grafting has not been carefully investigated. Methods Forty female patients requiring breast augmentation with fat grafting were randomly assigned into two groups. The retromammary group received 2/3 fat into the retromammary space and the other 1/3 into the subcutaneous and retropectoral planes. The retropectoral group received 2/3 fat into the retropectoral plane and the other 1/3 into the subcutaneous and retromammary planes. The fat grafting result at 6 months was assessed by 3D laser surface scanning and then ultrasound. Any complications were recorded during follow-up. Samples from a patient who underwent fat grafting for 6 months was obtained and histological examination was conducted. Results No significant difference in the retention rate after 6 months was observed between the two groups (retromammary group: 35.9% ± 6.6; retropectoral group: 39.3% ± 5.1, p = 0.1076). The retromammary grouphad a higher incidence of oil cyst formation than the retropectoral group. Histological examination showed that there were more oil cysts and mac2 positive macrophage infiltration in the fat cells in retromammary group, while retropectoral group had more small-size adipocytes. Conclusion Although fat grafting into the retropectoral plane did not provide a superior fat graft retention rate, it did lower the incidence of complications. The retropectoral space show great potential to become a favorable recipient site.